ALTERNATIF PENYELESAIAN SENGKETA YANG DILAKUKAN OLEH PIHAK YANG BERPERKARA TERKAIT PERJANJIAN PEMBIAYAAN KONSUMEN DENGAN JAMINAN FIDUSIA MAUPUN HAK TANGGUNGAN - Deviana Yuanitasari, Larasati Anyufa, Aam Suryamah dan (Normative Jurnal Ilmiah Hukum, 2021)
Consumer financing agreement with fiduciary guarantee or mortgage is one form of arbitration agreement. If there are problems such as creditors making withdrawals of objects or objects that are used as collateral rights or mortgage rights in the form of vehicles, both cars and motorbikes, because the debtor is unable to pay installments and defaults on the consumer financing agreement that has been agreed between the two, in practice many people have not know and understand where this dispute will be resolved. Then there is a legal disharmony between the Consumer Protection Act and the Financial Services Authority Regulation regarding Alternative Dispute Resolution Institutions in the Financial Services Sector which creates legal uncertainty in society. This study uses a normative juridical approach in this study in the form of library research and using analytical descriptive. The purpose of this research is to shed light on the legal disharmony that causes legal uncertainty in society regarding the settlement of financing disputes.